Hubungan Pemahaman Pelayanan Dan Panggilan Dengan Kesetiaan Pengerja Di Gereja - Wirianto Ng; Gundari Ginting; Lukgimin Aziz (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
This study aims to determine the existing relationship, both partially and mutually between understanding of servanthood and calling to serve and faithfulness in the ministry of all workers. The place of this research was conducted at My Family GBI. The research method used was an ex post facto pattern and quantitative. They concluded that there was a linear and significant relation between variable X1 (understanding of servanthood) and variable Y (faithfulness in ministry in church). So does X1 and X2 and Y. Every worker to realize that they were saved by God and repay God’s kindness by serving Him in church. It is recommended that this research can be used as one of the guidance as a foundation of ministering life by servants in God’s field.